A trained communication partner’s use of responsive strategies in aided communication with three adults with Rett syndrome: A case report - Wandin, Helena; Lindberg, Per; Sonnander, Karin (Frontiers in Psychology, 2022)
Purpose: To explore and describe a trained communication partner’s use of responsive strategies in dyadic interaction with adults with Rett syndrome. Introduction: Responsive partner strategies facilitate social, communicative, and linguistic development. The common feature is that the communication partner responds contingently to the other’s focus of attention and interpret their acts as communicative. Research on responsive partner strategies that involves individuals with significant communication and motor disabilities remains sparse and similarly if, and how, the use of communication aids impacts on the partner’s use of responsive strategies. Materials and methods: A therapist, trained in responsive partner strategies and aided communication interacted during 14 sessions with each of three participants. The participants were adults with Rett syndrome. A gaze-controlled device and responsive strategies were used during all sessions. The Responsive Augmentative and Alternative Communication Style scale (RAACS) was used to assess the partner’s responsiveness. RAACS consists of 11 items including ratings of to what extent the partner is being attentive to, confirms and expands the individual’s communication. During eight of the 14 sessions, aided AAC Modelling was also used, i.e. the communication partner pointed at symbols on the gaze-controlled device while interacting. In addition to RAACS, each time the communication partner confirmed or expanded on communication when a) the participants used the gaze-controlled device and b) the participants did not use the gaze-controlled device was counted. Descriptive statistics were used to present the results. Non-parametric tests were used to compare means between the two conditions and between participants. Results: Inter-rater agreement for the different items ranged from 0.73-0.96 and was thus found to be fair to excellent. The communication partner’s use of responsive strategies varied when communicating with different participants and the scores were higher when aided AAC modeling was used. The communication partner’s number of responses and use of responsive strategies were higher when the participants communicated through a gaze-controlled device. Conclusions: The communication partner’s use of responsive and scaffolding strategies is not a fixed construct but varies in interactions with different non-speaking persons as well as whether the non-speaking person uses a gaze-controlled device with digitized speech or not.